As trilhas culturais de deslocamento e a paisagem dos sistemas da Agricultura Familiar no projeto de assentamento Vila Amazônia-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The Cultural Displacement Trails (TCD) are references of geographic facts in the Vila Amazônia Settlement Project in the municipality of Parintins (AM), as they occur in a dynamic through the relation of interaction of man to the forms of spatial-temporal ordering. Thus, it was sought to understand the cultural impression attributed to the physiognomy of the landscape in the use of cultural trails in the system of family agriculture in space-time? As a research hypothesis: landscape physiognomy is established with family farmers' relationships with the environment and the complex interactions of TCD circularity in family farming systems in the Vila Amazonia Settlement Project. The methodological orientations were directed to a case study (YIN, 2005) using interdisciplinary methods of bibliographic research, pre-test, geographic and phytogeographic inventory, cultural trails, field diary and field research, with a complex and systemic approach ( MORIN, 2002). The chapters correspond to one objective: Chapter I - The geography of complexity in the context of landscape physiognomy: cultural trails; Family agriculture unit; landscape; Space time; Geoenvironment deals with the foundation of theoretical assumptions. Chapter II - Geoenvironments of the cultural trails of displacement in a family agriculture system and the impression of the landscape in space-time in the complexity of the interaction between society and nature and culture presents the results of the inventory of TCD present in the properties. Chapter III - Management of the geoenvironments of the family agriculture unit and the potential for tourism in rural areas points to the understanding of the variable elements of the landscape. Finally, Chapter IV - Cultural trails of displacement in properties and their use in activities in a family agriculture system in the space-time relationship presents the results of the diagnosis performed on the properties, as well as the identification of the management in the geoenvironments and the indications in the prognosis on The potential of tourism in rural areas. As a result, the systemic description of the complex interaction of the biogeographic characteristics established with the sociocultural relationship to the impression of the landscape physiognomy in the use of TCD in a family-based agriculture system in space-time in PA Vila Amazônia was obtained. For the planning and development of Tourism in the Rural Area.
Keywords: Trilhas de Deslocamento; Agricultura Familiar; Paisagem; CIÊNCIAS HUMANAS: GEOGRAFIA: GEOGRAFIA REGIONAL